2020
DOI: 10.1101/2020.03.02.973263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visibility Graph Based Community Detection for Biological Time Series

Abstract: MotivationTemporal behavior is an essential aspect of all biological systems. Time series have been previously represented as networks. Such representations must address two fundamental problems: (i) How to create the appropriate network to reflect the characteristics of biological time series. (ii) How to detect characteristic temporal patterns or events as network communities. General methods to detect communities have used metrics to compare the connectivity within a community to the connectivity one would … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…the nodes v i and v j are connected if the node v j is visible from the node v i and vice versa, therefore the resulting graph is undirected (for more details on the properties of VGs, see [36]). In general, there are two ways to construct a network (graph) from a time-series: the horizontal visibility graph (HVG) [39,101,102] and the natural visibility graph (NVG) [103][104][105], the former is more sparse than the latter case and in this work we focus on the NVG. In Fig.…”
Section: Visibility Graphmentioning
confidence: 99%
“…the nodes v i and v j are connected if the node v j is visible from the node v i and vice versa, therefore the resulting graph is undirected (for more details on the properties of VGs, see [36]). In general, there are two ways to construct a network (graph) from a time-series: the horizontal visibility graph (HVG) [39,101,102] and the natural visibility graph (NVG) [103][104][105], the former is more sparse than the latter case and in this work we focus on the NVG. In Fig.…”
Section: Visibility Graphmentioning
confidence: 99%
“…Those studies show different time series analysis in plasmas. However, not only fractals and multifractals could be useful in the study of time series, complex networks, particularly the Visibility Graph method, allow for a simple and direct time series analysis in self-organized critical phenomena, such as earthquakes [ 37 ], macroeconomic systems [ 38 ], or biological systems [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…VG is a tool to convert a given time series to a network and plays an essential role in determining the properties of nonlinear dynamical systems. Many statistical [14] and topological [15] aspects of VGs have been studied numerically and analytically, making it a standard powerful tool to study various systems like earthquakes [16], economics [17], ecology [18], neuroscience [19,20], and biology [21]. An important step towards an understanding the scaling properties of VGs was taken by Lacasa, who showed that a self-similar time series converts into an SF network, emphasizing that the power-law degree distributions are related to the fractality [14,22].…”
mentioning
confidence: 99%